Collective Intelligence: A New Model of Business Management in the Big-Data Ecosystem - Figueroa, Juan Luis Peñaloza; Pérez, Carmen Vargas (European Journal of Economics and Business Studies, 2018)
We are immersed in a world characterized by globalization, the widespread use of technology, the transition from administrative management to smart management, the networking of companies and the use of knowledge as an intangible asset, which raises the need for a review of the logic and practice of current business management. This situation requires rethinking and assessing the validity of these management systems to respond to changes in the business environment and market volatility. Our interest is twofold. The first is to study how different sets of business factors collectively work to get the company to operate and manage change, volatility and uncertainty within the Big-Data ecosystem framework. The second is to lay the foundations for the development of a management proposal based on collective intelligence (CI), whose key factors are interaction, interactive learning, distributed collaboration and the valorisation of knowledge in all its dimensions.